High Sensitive Directional Twist Sensor Based on a Mach–Zehnder Interferometer - Shujie Duan; Weiliang Liu; Cuiting Sun; Hang Jiang; Chong Yao; Kai Zhang; Xingyu Bai; Wen Wang; Cunlian Lu; Tao Geng; Feng Peng; Libo Yuan (IEEE Photonics Journal, 2018)
A new type of Mach-Zehnder interferometer (MZI) is proposed to measure twist and temperature. The sensor contains a pretwisted taper and a ball. The pretwisted taper is made by pretwisted, and then, thermally tapering along a single-mode fiber, to induce permanent spiral distortion in the fiber. The experimental results indicate that the sensor has higher twist sensitivity. Twisting the sensor for counterclockwise and clockwise direction, the twist sensitivities of Dip 1584 nm are -0.378 and 0.083 nm/(rad/m), respectively, and the twist sensitivities of Dip 1685 nm are -0.117 and 0.089 nm/(rad/m), respectively. Meanwhile, the twist direction can be determined by the value of the twist sensitivities. The temperature sensitivities of Dip 1584 and Dip 1685 nm are 63 pm/°C and 74 pm/°C, respectively. The feasibility of measuring the torsion and temperature characteristics has been experimentally confirmed. Thus, the proposed MZI sensor can be used to measure twist and temperature and discriminate twist direction.